The Role of Social Factors in Explaining Crime - Siti Nur Zahara, Hamzah; Lau, Evan (General Association of Economists From Romania (GAER), 2013)
Utilizing Malaysia data from 1973 to 2008, the study reveals that crime can be influenced by population, fertility, unemployment, and GDP in either the long-run or short-run period. This study also further analysed beyond sample estimations of the variables involved and found that although violent crime can be explained in the short-run only from the VECM analysis, it is found to be explained by other explanatory variables in the long-run of beyond sample for at least 50 years ahead. It is important for policy makers to focus in both social structure and economic conditions to help prevent crime in the long-run.